Uncovering the reasons behind irregular visits by patients with type 2 diabetes mellitus - Kuntari, Titik; Khotijah, Alfreda Amelia; Basya, Hana Nuraisa; Cakranegara, Rama; Ariant, Zinedine Yusuf; Handayani, Nina Tiwi (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Type 2 diabetes mellitus (DM) is a non-communicable disease with an increasing incidence. DM is associated with deaths caused by several complications. One of the efforts to manage DM is to control blood glucose by maintaining regular check-ups and treatment compliance. Unfortunately, many people with DM still need to visit health facilities regularly.Purpose: This study aimed to explain the factors associated with the irregularity of type 2 DM patients having check-ups at the public health center (puskesmas).Methods: This cross-sectional study used the medical record data from Grabag II Public Health Center. The subjects were 135 outpatients with type 2 DM and complete medical records.Results: The results showed that visit irregularity was significantly associated with sex (OR = 3.8; 95% CI = 1.12-12.79), distance from home (OR = 0.2; 95% CI = 0.06-0.52), and duration of diagnosis (OR = 0.3; 95% CI= 0.12-0.85), but not with age, insurance, comorbidities, and types of therapy.Conclusion: Factors associated with type 2 diabetes mellitus patients' irregular visits to Puskesmas are sex, distance from home, and duration of diagnosis. Educational interventions at all levels of society should be carried out to increase knowledge about DM and the importance of regular check-ups and medication